(3GdQjGOI hGOGQI efXeGJ GdGYeGds - (3HdGd Nda(B, (3GdScGfIs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2008)
(3Gf GdJWhQ GdJcfhdhLj hGdYdej aj efXeGJ GdCYeGd GdMOjKI bO SGYO Ydi HdhQI cKjQ ef GdefXeGJ GdQjGOjI aj bWGYGJ eNJdaI ef GdGYeGd(B. (3hNUhUG eY GROjGO GdefGaSI GdYGdejI hXghQ YhGed CNQi dJUHM GdefXeGJ GcKQ QjGOjI, hGSJZdGd GdaQU GdGSJKeGQjI HGdShb ef NdGd GdEHOGY hGdGHJcGQ, hcPdc YedjGJ GdQjGOI CUHMJ ef GdEOGQI GdESJQGJjLjI dCYeGd gPg GdefXeGJ(B. (3hJfTC GdefXeGJ GdQjGOjI ef NdGd fhYjf ef GdYedjGJ geG(B: (3GdChd(B: (3JWhjQ CfeGW LOjOI ef GdGYeGd ShGA GcGf ef NdGd GdEHOGY GdOGNdj Ge GdeTGQcI aj GdeNGWQI (B. (3GdBNQ(B: (3jJe ef NdGd JWhjQ GdefXeGJ HhGSWI GdJMOjK GdGSJQGJjLj Gh GdJcGed eG Hjf GdehGQO(B. (3hJSJWjY GdefXeGJ GdQjGOjI GdONhd Gdi GdCShGb HhGSWI efJLGJ LOjOI heNGWQI LOjOI haQU LOjOI, ef NdGd GdGSJaGOI ef YfGUQ eQJHWI HPdc ShGA CcGfJ HGdEHOGY Ge GNP GdNGWQI hGdeZGeQI hGdGSJbdGdjI hGdGHJcGQ hGdejRI GdJfGaSjI hGdJaQO, hYfGUQ eQJHWI HGdHjFI hGdCaQGO hGdefXeGJ(B. (3hGf GdefXeGJ GdQjGOjI HMGLI Gdi EOGQI bGOQI Ydi EjLGO fhY ef GdJfGZe Hjf eG JeJdcg ef eYQaI cdjI hbOQGJ ajfI(B. (3hGdJNWjW GdGSJQGJjLj hGeJdGc GdQDjI GdKGbHI dCgOGa GdefXeI GdQjGOjI, hUhdkG HgG Gdi eQcR JfGaSj ddhdhL Gdi YGde GdefXeGJ GdeJejRI, hMJi jJMbb Pdc GdeQcR aGf gfGc GdYOjO ef GdeMGhQ GdYedjGJjI GdJj Ydi GdefXeGJ GdQjGOjI Gf JJHfGgG dJLSjOgG aj HfGFgG GdJfXjej cGdGHJcGQ hGdEHOGY hGdHMK hGdJWhjQ hGdbGYOI GdeYQajI hGdeeGQSGJ GdEOGQjI (B. (3hef gfG JHRQ CgejI gPG GdcJGH aj GdMOjK Yf ehVhY GdQjGOI hEOGQI efXeGJ GdGYeGd(B. (3hJqe JbSjeg Gdi GMOi YTQ aUdkG(B. (3JfGhd GdaUd GdGhd(B: (3JhVjMG deaghe GdQjGOI hGdefXeGJ GdQjGOjI hGdQjGOj, hGdNUGFU GdeQJHWI Hge hGdYbdjI GdQjGOjI, GeG GdaUd GdKGfj(B: (3abO JfGhd GSJQGJjLjGJ GdQjGOI hOhQgG aj JMbjb GdEHOGY hGdejRI GdJfGaSjI defXeGJ GdCYeGd GeG GdaUd GdKGdK(B: (3abO JfGhd GdQjGOI hGdeTGQjY GdUZjQI hOhQgG aj JMbjb GdfLGM dgG, hGdjI EfLGR GdeTGQjY GdUZjQI hJWhjQgG(B. (3GeG GdaUd GdQGHY(B: (3abO JfGhd NWI GdYed hBdjI JMVjQgG hJfajPgG hechfGJgG hCSHGH aTdgG hGNJjGQ ehbY GdeTQhY(B. (3GeG GdaUd GdNGeS(B: (3abO JfGhd GdNWI GdJShjbjI hGdeRjL GdJShjbj hbfhGJ GdJhRjY hGdGSJQGJjLjGJ GdJShjbjI GdeDKQI Ydi efXeGJ GdCYeGd(B. (3GeG GdaUd GdSGOS(B: (3JfGhd NWI GdYedjGJ hBdjI GOGQI GdEfJGL hGdYedjGJ aj GdefXeI, GeG GdaUd GdSGHY(B: (3JfGhd NWI GdJehjd heUGOQ GdJehjd hbQGQGJ GdJehjd hGdJNWjW GdJehjdj(B. (3GeG GdaUd GdKGef(B: (3JfGhd GdQjGOI hGdCYeGd GdGdcJQhfjI hCgejI GdGfJQfJ hGdehbY GdGdcJQhfj aj JWhjQ NOeGJ efXeGJ GdCYeGd(B. (3GeG GdaUd GdJGSY(B: (3aJfGhd GdQjGOI hGdYhdeI hcja ddefXeGJ GdQjGOjI Gf JJLg fMh GdYGdejI hJMbjb GdqejRI GdJfGaSjI(B. (3CeG GdaUd GdYGTQ(B: (3abO JfGhd GdeTJQjGJ hEOGQJgG hhXGFagG, hGdeNRhf hfXe GdQbGHI Ydjg hUQag hLQOg(B. (3hGNJJe GdcJGH HGdaUd GdMGOj YTQ(B: (3GdPj JfGhd GdQjGOI aj GdGQOf heG gj GdbWGYGJ GdGbJUGOjI GdQjGOjI aj GdGQOf(B. (3gPG hbO JVefJ LejY aUhd GdcJGH CSFdI eNJGQI aj fgGjI cd aUd dJchf eYjfI dbGQFj gPG GdcJGH aj eOi Jage ehVhYGJg(B.s
(3HjHdjhZQGajG U(B.352s
Keywords: (3GOGQI GdGYeGds; (3GOGQI GdJfajPjIs; (3GOGQI GdeTGQjYs